Beyond Case Studies: Expanding the Constructionist Framework for Social Problems Research - Best, Joel (Qualitative Sociology Review, 2015)
Most constructionist analyses of social problems are case studies; these focus attention on the particulars of the case at hand. Analysts have devoted less attention to the ways cases can be connected. This paper presents a typology of such connections, based on five elements: the problem, the frame, the claims-makers, place, and time. The typology identifies ways each of these elements can serve as a basis for connecting different campaigns to construct social problems.